2015
DOI: 10.4314/tjpr.v14i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Permeation Kinetic Studies of Flurbiprofen Gel

Abstract: cps, respectively. No irritation or lesions (erythma, redness and ulceration)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…44 In addition, previous studies have used synthetic membranes to determine the permeation of flurbiprofen or ibuprofen gel; however, although easily resourced, inexpensive, and structurally simpler, they do not reflect what may happen in vivo. 32,45,46 An important limitation of our study was the use of cadaver tissue, which may result in drug penetration speed that does not truly reflect live tissue, where a blood supply is present. In addition, the absence of inflammation and the lack of a mucosal barrier may modify drug penetration.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition, previous studies have used synthetic membranes to determine the permeation of flurbiprofen or ibuprofen gel; however, although easily resourced, inexpensive, and structurally simpler, they do not reflect what may happen in vivo. 32,45,46 An important limitation of our study was the use of cadaver tissue, which may result in drug penetration speed that does not truly reflect live tissue, where a blood supply is present. In addition, the absence of inflammation and the lack of a mucosal barrier may modify drug penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated poor dermal and transdermal delivery of chrysin and quercetin [5,[8][9][10][11]17]. The literature reports that solvents commonly used in cosmetics and dermatological products can influence release and skin penetration processes [17][18][19][20][21][22][23][24]. In the present study, the influence of two solvents -PG and PEG 400on the release and the skin retention of two flavonoidschrysin and quercetinwas investigated.…”
Section: Discussionmentioning
confidence: 97%
“…While the dissolution of the flavonoids in the solvents may be assumed to be the main determinant of the release rate, the skin retention appears to be additionally impacted by interactions of the used solvents with the skin barrier . The ability of the used solvent to penetrate into the skin and to interact with that barrier seemed to be necessary for providing an enhancement of the skin retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not currently plausible to investigate the penetration of flurbiprofen into human pharynx tissue in vivo and, as such, alternative methods of investigation must be used. The Franz diffusion cell method has been used previously to mimic physiological and anatomical conditions to allow the study of diffusion through various tissues, 31 , 32 including human pharynx tissue. 23 , 25 This ex vivo model was developed to mimic the clinical scenario as closely as possible, 25 using full-thickness cadaveric pharynx tissue, which provides a close match to the physiological and anatomical conditions of the human pharynx.…”
Section: Discussionmentioning
confidence: 99%